2017
DOI: 10.3892/mmr.2017.8243
|View full text |Cite
|
Sign up to set email alerts
|

Less hippocampal neuronal death in young gerbils following transient global cerebral ischemia is associated with long‑term maintenance of insulin‑like growth factor�1 and its receptors in the hippocampal CA1 region

Abstract: Insulin-like growth factor 1 (IGF-1) is a well-known growth factor with well-defined neuroprotective effects against cerebral ischemia. However, the age-dependent differences in the expression of IGF-1 and its receptor (IGF-1R) in the brain following transient cerebral ischemia (TCI) have not been elucidated. In the present study, the differences in IGF-1 and IGF-1R in the gerbil hippocampal CA1 region of young and adult gerbils 5 min following TCI were determined. Seven days following TCI, the neuronal death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In addition, the number of dead pyramidal neurons (DND) at 7 and 15 days after tFI was significantly lower in the young ischemia group than that in the adult ischemia group. This result is consistent with our and other previous studies reporting that tFI-induced DND in the hippocampal CA1 in young gerbils was shown in fewer pyramidal neurons and more delayed in time than that shown in adult gerbils ( 9 , 24 , 25 ). Taken together, we suggest that the difference of DND between young and adult groups might be associated with the differences of various factors to affect DND, including glial activation, inflammatory cytokine expression and NMDA receptor expression ( 26 28 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, the number of dead pyramidal neurons (DND) at 7 and 15 days after tFI was significantly lower in the young ischemia group than that in the adult ischemia group. This result is consistent with our and other previous studies reporting that tFI-induced DND in the hippocampal CA1 in young gerbils was shown in fewer pyramidal neurons and more delayed in time than that shown in adult gerbils ( 9 , 24 , 25 ). Taken together, we suggest that the difference of DND between young and adult groups might be associated with the differences of various factors to affect DND, including glial activation, inflammatory cytokine expression and NMDA receptor expression ( 26 28 ).…”
Section: Discussionsupporting
confidence: 94%
“…TNF-R1, tumor necrosis factor receptor 1; CA1, cornu ammonis 1; SP, stratum pyramidale; tFI, transient forebrain ischemia; ROD, relative optical density; SO, stratum oriens; SR, stratum radiatum. DND in the hippocampal CA1 in young gerbils was shown in fewer pyramidal neurons and more delayed in time than that shown in adult gerbils (9,24,25). Taken together, we suggest that the difference of DND between young and adult groups might be associated with the differences of various factors to affect DND, including glial activation, inflammatory cytokine expression and NMDA receptor expression (26)(27)(28).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Protein phosphatase binding is closely related to CIS, for example, the insulin-like growth factor 1 receptor often facilitates cell survival, cell proliferation, metabolism, and stress resistance triggered by the tyrosine autophosphorylation of its β chains (40). In addition, our previous findings indicated that insulin-like growth factor 1 receptor may be an alternative target for preventing the cerebral ischemic injury (41).…”
Section: Discussionmentioning
confidence: 95%